Life System Modeling and Intelligent Computing International Conference on Life System Modeling and Simulation, LSMS 2010, and International Conference on Intelligent Computing for Sustainable Energy and Environment, ICSEE 2010, Wuxi, China, September 17-20, 2010. Proceedings, Part II - Li, Kang.; Li, Xin.; Ma, Shiwei; Irwin, George W.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This book constitutes the refereed proceedings of the International Conference on Life System Modeling and Simulation, LSMS 2010, and International Conference on Intelligent Computing for Sustainable Energy and Environment, ICSEE 2010, held in Wuxi, China, in September 2010. The papers are organized in topical sections on intelligent modeling, monitoring, and control of complex nonlinear systems; modeling and simulation of societies and collective behaviour; advanced theory and methodology in fuzzy systems and soft computing; biomedical signal processing, imaging, and visualization; computational intelligence in utilization of clean and renewable energy resources; innovative education for sustainable energy and environment; and intelligent methods in power and energy infrastructure development.
The First Section: Advanced Evolutionary Computing Theory and Algorithms -- Co-Evolutionary Cultural Based Particle Swarm Optimization Algorithm -- Non-cooperative Game Model Based Bandwidth Scheduling and the Optimization of Quantum-Inspired Weight Adaptive PSO in a Networked Learning Control System -- Modified Bacterial Foraging Optimizer for Liquidity Risk Portfolio Optimization -- A Combined System for Power Quality Improvement in Grid-Parallel Microgrid -- A Distance Sorting Based Multi-Objective Particle Swarm Optimizer and Its Applications -- A Discrete Harmony Search Algorithm -- CFBB PID Controller Tuning with Probability based Binary Particle Swarm Optimization Algorithm -- A Novel Cultural Algorithm and Its Application to the Constrained Optimization in Ammonia Synthesis -- Pareto Ant Colony Algorithm for Building Life Cycle Energy Consumption Optimization -- Particle Swarm Optimization Based Clustering: A Comparison of Different Cluster Validity Indices -- A Frequency Domain Approach to PID Controllers Design in Boiler-Turbine Units -- An Estimation of Distribution Algorithm Based on Clayton Copula and Empirical Margins -- Clonal Selection Classification Algorithm for High-Dimensional Data -- The Second Section: Advanced Neural Network Theory and Algorithms -- A General Framework for High-Dimensional Data Reduction Using Unsupervised Bayesian Model -- The Model Following Neural Control Applied to Energy-Saving BLDC Air Conditioner System -- Develop of Specific Sewage Pretreatment and Network Monitoring System -- Application of Radial Basis Function Neural Network in Modeling Wastewater Sludge Recycle System -- Improved Stability Criteria for Delayed Neural Networks -- Aplication of the Single Neuron PID Controller on the Simulated Chassis Dynamometer -- Research on the Neural Network Information Fusion Technology for Distinguishing Chemical Agents -- The Third Section: Innovative Education in Systems Modeling and Simulation -- Simulating Energy Requirements for an MDF Production Plant -- Three-Dimensional Mesh Generation for Human Heart Model -- Interactive Identification Method for Box-Jenkins Models -- Research on Nano-repositioning of Atomic Force Microscopy Based on Nano-manipulation -- Research on Expression Method of a Unified Constraint Multi-domain Model for Complex Products -- The Fourth Section: Intelligent Methods in Developing Vehicles, Engines and Equipments -- An Automatic Collision Avoidance Strategy for Unmanned Surface Vehicles -- Research on Fire-Engine Pressure Balance Control System Based Upon Neural Networks -- The Summary of Reconstruction Method for Energy Conservation and Emission Reduction of Furnace -- Osmotic Energy Conversion Techniques from Seawater -- The Fifth Section: Fuzzy, Neural, and Fuzzy-Neuro Hybrids -- Vibration Monitoring of Auxiliaries in Power Plants Based on AR (P) Model Using Wireless Sensor Networks -- Performance Prediction for a Centrifugal Pump with Splitter Blades Based on BP Artificial Neural Network -- Short-Term Traffic Flow Prediction Based on Interval Type-2 Fuzzy Neural Networks -- Neural Network and Sliding Mode Control Combining Based Reconfigurable Control -- Study on Membrane Protein Interaction Networks by Constructing Gene Regulatory Network Model.
Keywords: Computer science; Computer software; Data mining; Information storage and retrieval systems; Computer simulation; Biometrics; Bioinformatics; Computer Science; Computational Biology/Bioinformatics.; Information Storage and Retrieval; Data Mining and Knowledge Discovery; Biometrics; Algorithm Analysis and Problem Complexity; Simulation and Modeling